ANALISIS GAYA HIDUP HALAL PADA BIDANG PARIWISATA DALAM PRESPEKTIF MAQASHID SYARIAH: STUDI OBJEK WISATA JALAN BRAGA BANDUNG - Atroba Mubarok, Uruban; Wahab, Abdul; Isnawati, Muridah; Mubarok, Atus Ludin (Pusat Studi Ekonomi, Publikasi Ilmiah dan Pengembangan SDM, 2025)
This research is motivated by the presence of global awareness of the need for tourism that is in harmony with Islamic principles. Braga street as a historical and cultural destination in Bandung has a high attraction but has not accommodated the needs of Muslim tourists optimally. The main problem lies in the gap between the potential of the area and the implementation of halal lifestyle values in accordance with maqashid sharia. The purpose of this study was to analyze the implementation of halal lifestyle in urban tourism areas and assess its suitability with the five principles of maqashid sharia: maintenance of religion, soul, mind, offspring, and property. This research used a qualitative approach with a case study method and a phenomenological approach. Data were collected through interviews with tourists and business actors, participatory observation, and documentation studies. The results showed that the application of halal lifestyle in Braga Street has not been structured, the availability of halal food, worship facilities, and sharia-friendly services is still limited. However, there is great potential to develop value-based and cultural halal tourism destinations, with support from local communities and government policies.